Firm's Characteristics And Capital Structure - Evidence From Firms In Northern Corridor Economic Region (NCER) Of Malaysia - Masron, Tajul Ariffin; Zulkafli, Abdul Hadi; Ibrahim, Haslindar (Universiti Sains Malaysia, 2011)
Study on capital structure of companies is abundant as it is reflecting the financial health of firm. Nonetheless, majority of them are either dealing with issues in developed countries or publicly listed companies only. We observed very limited studies on non-listed companies, including small and medium companies.